2010 IEEE International Conference on Image Processing 2010
DOI: 10.1109/icip.2010.5651637
|View full text |Cite
|
Sign up to set email alerts
|

Color exploitation in hog-based traffic sign detection

Abstract: We study traffic sign detection on a challenging large-scale realworld dataset of panoramic images. The core processing is based on the Histogram of Oriented Gradients (HOG) algorithm which is extended by incorporating color information in the feature vector. The choice of the color space has a large influence on the performance, where we have found that the CIELab and YCbCr color spaces give the best results. The use of color significantly improves the detection performance. We compare the performance of a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(40 citation statements)
references
References 7 publications
0
40
0
Order By: Relevance
“…Given the sign category, a second classification is performed. A colour-HOG feature is used in this case, which is created by concatenating the HOG feature of each colour channel of the image in the CIELab colour space (Creusen et al, 2010). This feature is again classified by means of SVM, and the type of the sign is finally retrieved.…”
Section: Point Cloud Projection On Images and Traffic Sign Recognitionmentioning
confidence: 99%
“…Given the sign category, a second classification is performed. A colour-HOG feature is used in this case, which is created by concatenating the HOG feature of each colour channel of the image in the CIELab colour space (Creusen et al, 2010). This feature is again classified by means of SVM, and the type of the sign is finally retrieved.…”
Section: Point Cloud Projection On Images and Traffic Sign Recognitionmentioning
confidence: 99%
“…The CIELab and YCbCr color spaces were used for different shapes of traffic signs by [32]. In particular, they have found that YCbCr space is suitable for segmentation of triangular signs.…”
Section: Ycbcr Color Spacementioning
confidence: 99%
“…The fog lamps type selection and calculation method were established by Yang [5] from the fog lamps longitudinal and transverse location and installation height, the fog lamps engineering design theory, in view of the fog lamp brightness and diameter. Much research has been done both at home and abroad from the fog area road traffic safety guidance [6][7][8], however, these researches focused more from the viewpoint of security equipment and modern network technologies for building guidance systems, rather than from the perspective of landscape color or design to improve road traffic safety in foggy areas.…”
Section: The Civil Engineering Journal 3-2017 -----------------------mentioning
confidence: 99%